2010
DOI: 10.3892/mmr_00000308
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 protects PC12 cells against β-amyloid-induced cell injury

Abstract: Abstract. excessive accumulation of β-amyloid (aβ) has been proposed as a pivotal event in the pathogenesis of alzheimer's disease. Possible mechanisms underlying aβ-induced neuronal cytotoxicity include oxidative stress and apoptosis. reactive oxygen species (roS) have been proposed to be involved in the apoptotic mechanism of aβ-induced cytotoxicity. Ginsenoside rb1 (Grb1), which is among the key compounds of ginsenoside, found in ginseng, may be a potent scavenger of roS. To examine the potential protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Gn Rb1 has been previously shown to exert cell protective effects against the toxicity induced by Aβ 42 (Qian, Han, Hu, & Shi, 2009) and Aβ 25-35 (X. Xie et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Gn Rb1 has been previously shown to exert cell protective effects against the toxicity induced by Aβ 42 (Qian, Han, Hu, & Shi, 2009) and Aβ 25-35 (X. Xie et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the development of hydrogen peroxide [26,27], glutamate [28], MPP+ [29] and β-amyloid-induced cell death [30]; however, the mechanism by which LPS leads to microglial toxicity remains obscure. In addition, it is noteworthy that G-Re has a protective effect with a markedly attenuated microglial response of caspase 3 activation (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ginseng possesses several important biological functions for human health, such as recovery and promotion of vitality, improvement of immune and metabolism systems, regulation of central nervous system, etc. [1, 2]. Ginseng native to the Province of Jilin, China, is often known as Jilin ginseng and estimated to produce 85% and 70% of the ginseng of China and the world, respectively.…”
Section: Introductionmentioning
confidence: 99%